Redemption Through Culture: Hungarian Cultural Diplomacy and Its English and American Perspectives in the 1920s - T. Molnár, Gizella; Tőke, Márton (AMERICANA E-journal of American Studies in Hungary, 2020)
This paper examines how the prolific Hungarian Minister of Culture in the interwar period, Kuno Klebelsberg shaped cultural diplomacy in the 1920s, with a specific focus on the relations between Hungary, the United Kingdom and the United States of America. After reviewing the many links between Klebelsberg and mainstream contemporary European education, politics, and culture, the paper illuminates Klebelsberg’s policy of science and scientific research, developing Hungarian participation in natural and technical sciences, and the strategic aims he prioritized in connection with these endeavors. Subsequently, the paper provides an in-depth analysis of Klebelsberg’s cultural diplomacy, his embeddedness in the ideals of a Hungary that is an integral part of Europe and that mends the injustices of the Treaty of Trianon through cultural efforts and not arms. Finally, the paper also investigates the globalizing efforts in Klebelsberg’s higher education policy, focusing especially on the system of Collegium Hungaricum he realized as well as the plans and goals that were not ultimately reached due to Klebelsberg’s death and the shift in policy priorities that followed.